2022
DOI: 10.33736/ils.4074.2022
|View full text |Cite
|
Sign up to set email alerts
|

Supremacy of English Language Proficiency: Identity Transmission and Transgression among Bangladeshi Graduates

Abstract: The study focuses on the language use of Bangladeshi graduates and how they deal with the local Bengali language with English as an international language. The study investigates whether the perception of ELP promotes identity transmission or transgression. The study is conducted with a mixed-method approach using a triangulation research design with a convergence model. Questionnaire data were collected from 370 respondents consisting of three groups of graduates according to educational qualifications, incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(38 citation statements)
references
References 35 publications
5
33
0
Order By: Relevance
“…Research by Islam et al (2022) delves into Bangladeshi immigrants' experiences and perceptions of their occupations in Canada, shedding light on the practical implications of language skills in securing better job opportunities. It has been reported that despite their higher education in Bangladesh, immigrants from Bangladesh face challenges in obtaining jobs in Canada because they do not have adequate English language skills.…”
Section: English Language Skill Demand-driven Job Opportunitiesmentioning
confidence: 99%
“…Research by Islam et al (2022) delves into Bangladeshi immigrants' experiences and perceptions of their occupations in Canada, shedding light on the practical implications of language skills in securing better job opportunities. It has been reported that despite their higher education in Bangladesh, immigrants from Bangladesh face challenges in obtaining jobs in Canada because they do not have adequate English language skills.…”
Section: English Language Skill Demand-driven Job Opportunitiesmentioning
confidence: 99%
“…For business students to secure a lucrative job and have a successful career, they must have a greater level of English proficiency (Louhiala & Kankaanranta, 2012;Taillefer, 2007;Haidar, 2019). Thus, according to a study of the literature, there have been relatively few research looking at how teachers and students perceive EMI in the context of the sub-continent (Tania & Phyak, 2022;Islam, Ramalingam & Hoque, 2022). We decided to explore how the EMI affected business students' academic performance in Pakistan as a result of this requirement for research.…”
Section: English As Medium Of Instruction (Emi)mentioning
confidence: 99%
“…The language used by a teacher in classroom affects the comprehension level of students and ultimately affects their performance in subject. According to studies (Vinke, 1995;Klaassen, 2001;Islam et al, 2022), classroom environment becomes less interactive when the subjects are being taught in English (L2) rather than in Dutch. Another study by Thøgersen and Airey, (2011) concluded that lecturers speak at a comparatively slow rate while delivering a lecture in English (L2) than in the native language resulting in fewer syllables per second.…”
Section: Emi and Academic Performancementioning
confidence: 99%
“…Language proficiency is considered a ladder to success in life (Afrin and Baines 2020). The trend commenced during the colonial period in this continent; during British rule, people in the elite class were fond of learning the English language (Islam et al 2022b). Although the British left this continent, they placed the English language among the people of the continent (Rahman et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As Bangladeshis are part of this continent, the country has to follow current trends as graduates try to stay up to date with progress in language and technology (Islam et al 2022b). In these circumstances, English is essential to empowering graduates to cope with the neoliberal trends in the economy and globalisation (Hamid and Rahman 2019;Kabir and Chowdhury 2021;Sultana 2022).…”
Section: Introductionmentioning
confidence: 99%